2023
DOI: 10.21203/rs.3.rs-3228742/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Contemporary Definitions of Infant Growth Failure and Neurodevelopmental and Behavioral Outcomes in Extremely Premature Infants at Two Years of Age

Abstract: Introduction: The association of 2-year neurodevelopmental and behavioral outcomes with in-hospital or post-discharge growth failure (GF) using contemporary definitions for preterm infants is unknown. Methods In a secondary analysis of a preterm cohort, changes in anthropometric z-scores were examined between birth and hospital discharge, and from discharge to 2 years. The 2-year evaluation included Bayley Scales of Infant Development (BSID-III) and Child Behavior Checklist (CBCL). Results Among 629 infants… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…(6)(7)(8)(9) Additionally, investigations have revealed the relationship between postnatal growth and long-term neurodevelopmental outcomes in ELBW infants, emphasizing the lasting consequences of growth challenges. (10)(11)(12)(13)(14) Variable degrees of catch-up were reported by different authors at different times postnatally. For instance, Raaijmakers et al conducted a comprehensive study that examined the postnatal growth patterns of ELBW infants for 11 years and identified that Catch-up growth (i.e., ΔZ-score >0.67 SDS) for weight was achieved during the first two years of life in only 9.9% of cases, for length in 13.7% of cases and for head circumference in 14.1% of cases.…”
Section: Introductionmentioning
confidence: 99%
“…(6)(7)(8)(9) Additionally, investigations have revealed the relationship between postnatal growth and long-term neurodevelopmental outcomes in ELBW infants, emphasizing the lasting consequences of growth challenges. (10)(11)(12)(13)(14) Variable degrees of catch-up were reported by different authors at different times postnatally. For instance, Raaijmakers et al conducted a comprehensive study that examined the postnatal growth patterns of ELBW infants for 11 years and identified that Catch-up growth (i.e., ΔZ-score >0.67 SDS) for weight was achieved during the first two years of life in only 9.9% of cases, for length in 13.7% of cases and for head circumference in 14.1% of cases.…”
Section: Introductionmentioning
confidence: 99%